A CRITICAL APPROACH TO CULTURE AND SOCIETY DEFINITIONS - Gunduz, Zafer (PEOPLE: International Journal of Social Sciences, 2017)
The point that is stressed by definitions of culture, which rely on its authenticity and considerations that it entails individuality (diversity), is its diversity. Being diverse and acknowledgement of authenticity of the diversity, involves forwardness in itself. Though the acknowledgement of diversity and the impression of integrity formed by the acknowledgement seem to pose a coherence, yet it bears a negative aspect internally. Despite so-called acknowledgement of diversity, coherence and integrity formation seem to be more important. Since coherence of the integrity is based on measures of the seeking subject, forwardness aims to preserve things that are available or to simply fill the gaps. Hence complexity and diversity bear a negative meaning for available things. Because of centered approach which basically is putting familiar things into a closer circle while putting others aside. It brings concretization to the culture. To the extent of concretization endeavor, it leads us to study culture as belonging to a society (the privatization aim here even breaks down culture to a subculture level). Concretization of culture itself might seem as understanding and acknowledgement of culture, however, the aim for making a definition involves detaching the existent from existence forms and from the environment that it exists in. This article is to discuss, with philosophical terms, how different cultures embrace sincerity in exposing themselves while interacting with other cultures given our definitions of culture and the seeking for multiculturalism. Thanks to developments in transportation and means of technology, different cultures and societies meet and interact easily. Though we have a heritage of drawing borders, these borders hardly preserve their existence. The issues under discussion have evolved from the endeavor to build a common identity-culture-society to acknowledgement of diversity and difference.